From NAFLD to MASLD – a new approach for the definition of fatty liver disease associated with metabolic dysfunction - Iwona Gorczyca-Głowacka; Łukasz Nawacki; Magdalena Dolecka-Ślusarczyk; Agnieszka Ciba-Stemplewska; Stanisław Głuszek (Studia Medyczne)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is common, affecting a quarter of the population. The pathogenesis of this disease is multifactorial and has been well known for years. After 40 years of using the binding definition of non-alcoholic fatty liver disease (NAFLD), in 2020 new criteria for the diagnosis of metabolic dysfunction-associated fatty liver disease (MAFLD) were proposed, which significantly simplified the diagnosis of the disease, and in 2023 another division of steatotic liver disease (SLD) was proposed based on the aetiology of the disease. The diagnosis of MASLD is clinically important because the presence of this disease significantly influences the prognosis related not only to hepatic but, above all, cardiovascular events.